Training on Transactional Language, Online Marketing, and Visual Picture-Arts on Social Media Platforms at Nursey Grape Kawali - Dian, Dian Ardiansah; R. Hozin, R. Hozin Abdul Fatah; Yayan, Yayan Rudianto (Nusantara Journal Of Management Business (NUMABI), 2025)
MSME (Micro, Small, and Medium Enterprises) is a strongly potential business encouraged by the Indonesian government. In the midst of the digitalization era and the advancements in Technology Industry 4.0, mastering technology has become a necessity for MSME actors to compete globally and survive in an increasingly competitive market. This series of advancements is marked by the presence of many marketplaces in the form of online applications, one of which is the Facebook application. The objective of this Community Service Program (PKM) is to provide training in Digital Marketing communication, creating pages/fan pages, setting up the layout of pages/fan pages, and also visual picture-arts in the Facebook Marketplace application so that MSME actors can utilize this platform to expand market reach, introduce products or services more effectively, and increase sales.